Dietary exposure to elements from the German pilot total diet study (TDS). Issue 12 (2nd December 2019) - Kolbaum, Anna Elena; Berg, Katharina; Müller, Frederic; Kappenstein, Oliver; Lindtner, Oliver
ABSTRACT: Dietary exposure of the German adult population to the elements aluminium, copper, mercury (and as methylmercury), manganese and lead were assessed using data from the first total diet study (TDS) in Germany. In this pilot TDS, performed 2014–2015, 246 food samples were purchased in the Berlin area, prepared 'as consumed', and subsequently analysed. Dietary exposure for the German adult population between 14 and 80 years of age was estimated by combining TDS data with individual consumption data from the German National Consumption Survey II (NVS II). Estimated mean and high-level dietary exposure values showed that none of the elements analysed exceeded toxicological reference values; neither was there an undersupply of essential elements. Assessments for methylmercury and lead in women of child-bearing age, in particular, showed no considerable elevated intake levels.